Policing Policy: Sheriff's Memorandum on ICE Holds - (:unkn) unknown (My University, 2014)
In this announcement, the Montrose County Sheriff's Office dictates that the Montrose County Jail will no longer hold individuals on an I-247 Form or Immigration and Customs Enforcement (ICE) Detainer alone.
Keywords: Sanctuary Policies; ICE form I-247